Stress distribution and failure load of multilayer and monolayer glass ceramic. - Archangelo, Karen Cristina; Penteado, Marcela Moreira; Dal Piva, Amanda Maria de Oliveira; Nogueira, Andrea Souza; Tribst, João Paulo Mendes; Borges, Alexandre Luiz Souto (Brazilian Dental Science, 2019)
This short report evaluated the differences in stress concentration and the load to fracture of multilayered and monolayer glass ceramic discs. Using a static structural analysis, the 3D model of the discs received a load of 150N and results in maximum principal stress were obtained. For the in vitro analysis, the samples (ø 12 mm) were submitted to a compressive test (100kgf, 1mm/min). The data was analyzed using one-way analysis of variance and Tukey test (?=5%). The monolayer group showed a lower stress peak (129.24 MPa) and higher load to fracture (118.38N) than the multilayered group with 211.04MPa and 48.34N, respectively. All samples presented catastrophic failure with its origin on the tensile surface. Therefore, the monolayer ceramic group showed superior mechanical behavior than the multilayered group.